Double-phase composite sodium ion battery positive electrode material and preparation method thereof

By introducing high entropy strategy and Sn doping into the positive electrode material of sodium ion battery, the composite ratio of P2/O3 is regulated, and the stability of oxide-based positive electrode materials is solved, and the circulation performance and stability are significantly improved.

CN119315026AActive Publication Date: 2025-01-14HEFEI INSTITUTE OF PHYSICAL SCIENCE CHINESE ACADEMY OF SCIENCES
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202411351775.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2025-01-14
Estimated Expiration
2044-09-26

AI Technical Summary

Technical Problem

The oxide-type cathode materials of sodium ion batteries are easily reacted with water or air, resulting in a decrease in electrochemical performance and stability. Their complex working mechanism and various phase transition behaviors affect the cyclic stability of the material.

Method used

A high-entropy strategy is used to randomly distribute multiple element ions at the cationic lattice point. By regulating the composite ratio of P2/O3 and the doping ratio of Sn, the irreversible phase change of the material is suppressed and the cyclic stability of the positive electrode material is improved.

Benefits of technology

Through high entropy effect and Sn doping regulation, the cycle stability and performance of the positive electrode material of sodium ion battery are significantly improved. The reversible discharge specific capacity in the first week increases, and the capacity retention rate increases by 15.28% after 100 cycles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119315026A_ABST
    Figure CN119315026A_ABST
Patent Text Reader

Abstract

The invention discloses a double-phase composite sodium ion battery positive electrode material which is characterized in that the double-phase composite sodium ion battery positive electrode material has a P2 / O3 two-phase composite structure, the chemical formula of the double-phase composite sodium ion battery positive electrode material is Na < 1-x > Fe < y > Ni < z > Mn Ti < v > Co < w > Sn < 1-y-z-u-v-w > O < 2 >, xlt; 1, 0lt; y, z, u, v and w are all smaller than 1 and larger than 0, and Fe, Ni, Mn, Ti, Co and Sn elements are all located in the transition metal layer and are arranged disorderly. According to the invention, by utilizing wet ball milling, Sn doping and a high entropy strategy, P2 / O3 two-phase positive electrode materials with different proportions are obtained, and the first-week reversible specific discharge capacity of a battery assembled by the positive electrode material with the molar content of Sn accounting for 2% of the molar weight of all elements in a transition metal layer reaches 113.92 mAh / g; and after 100 cycles, the capacity retention ratio is 61.38%, which is improved by 15.28% compared with that of the non-doped Sn.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to a dual-phase composite sodium ion battery positive electrode material and a preparation method thereof. Background Art

[0002] With the growing demand for clean energy, the research on sodium-ion batteries has become a potential option to meet the demand for energy storage. As a high-energy-density energy storage technology that can replace lithium-ion batteries, sodium-ion batteries have the advantages of abundant sodium resources and sustainability. The positive electrode materials of sodium-ion batteries mainly include oxides, polyanions, Prussian blue and organic materials, among which oxide positive electrode materials have attracted much attention due to their unique structural characteristics.

[0003] Oxide cathode materials are mainly layered oxides, which have a periodic layered structure and high specific capacity and voltage, and are ideal candidate cathode materials. However, they easily react with water or air, resulting in a decrease in electrochemical performance and stability. Therefore, the storage environment must be strictly controlled and they cannot be stored in the air for a long time. Compared with lithium-ion batteries, which only have layered oxide cathodes of three elements, Mn, Co, and Ni, that have reversible electrochemical activity, sodium-ion batteries have a wider range of choices. The transition metals from Ti to Ni in the fourth period are highly active, and their working mechanism is more complex, often accompanied by multiple phase change behaviors.

[0004] The definition of entropy was first proposed by Clausius in 1865 as a physical quantity used to describe the disorder of a system. "High entropy" refers to the highly disordered state of a system, including conformational entropy, vibrational entropy, and magnetic dipole entropy. Here, we introduce the high entropy strategy into the positive electrode materials of sodium-ion batteries. In layered oxide positive electrode materials, the introduction of conformational entropy is achieved by randomly distributing a variety of different element ions on the cation lattice points. In alloy systems, for five or more components, those with a conformational entropy greater than or equal to 1.5R are defined as high entropy. According to the Gibbs-Helmholtz equation (ΔG=ΔH-T·ΔS), when the entropy value of a system can balance or exceed its enthalpy, the system tends to be entropy stable. The higher the entropy value, the more stable the crystal structure. In high-entropy oxides, the same cation lattice point can be occupied by different element ions, and different elements randomly occupy lattice positions, and the overall structure is a stable solid solution. Due to the disordered arrangement of atoms inside the structure, not only the stability of the crystal structure is enhanced, but also lattice distortion is easily caused, so that high-entropy materials exhibit a series of excellent properties, such as improving ionic conductivity and enhancing structural stability. Summary of the invention

[0005] The present invention provides a positive electrode material for a dual-phase composite sodium-ion battery and a preparation method thereof. Through high-entropy regulation and Sn substitution strategies, the regulation of the P2 / O3 dual-phase composite ratio is successfully achieved, and the irreversible phase transformation of the material is inhibited, thereby improving the cycle stability of the positive electrode material.

[0006] The technical solution of the present invention is as follows:

[0007] A positive electrode material for a dual-phase composite sodium-ion battery, which has a P2 / O3 dual-phase composite structure, and the chemical formula is Na 1- x Fe y Ni z Mn u Ti v Co w Sn 1-y-z-u-v-w O2, where 0 < x < 1, 0 < y, z, u, v, w are all less than 1 and greater than 0, and the elements Fe, Ni, Mn, Ti, Co, and Sn are in the same transition metal layer and are arranged disorderly.

[0008] In a further embodiment, x is 0.05 to 0.3, y is 0.1 to 0.3, z is 0.1 to 0.3, u is 0.1 to 0.3, v is 0.1 to 0.3, w is 0.1 to 0.3, and 0 < 1 - y - z - u - v - w ≤ 0.3.

[0009] In a further preferred embodiment, w is 0.14 to 0.18, and 0 < 1 - y - z - u - v - w ≤ 0.06.

[0010] In a further embodiment, the mass ratio of the P2 phase to the O3 phase is 15:85 to 25:75.

[0011] The second object of the present invention is to provide a preparation method for the above positive electrode material for a dual-phase composite sodium-ion battery, comprising the following steps:

[0012] (1) Adding a sodium source, an iron source, a nickel source, a manganese source, a titanium source, a cobalt source, and a tin source to a dispersant for ball milling and mixing, and drying the mixture to obtain a precursor;

[0013] (2) Calcining the precursor, then cooling it in the furnace to 100 °C, and immediately transferring it to an argon glove box to obtain the positive electrode material for a dual-phase composite sodium-ion battery.

[0014] In a further embodiment, in step (1), the dispersant is acetone, ethanol, or toluene, and the time for ball milling and mixing is 4 to 10 h;

[0015] In a further embodiment, in step (2), the calcination is a three-stage calcination, specifically: heating to 300°C-400°C at a heating rate of 3°C / min in an air atmosphere and keeping warm for 3h-5h; then heating to 500°C-600°C at a heating rate of 3°C / min and keeping warm for 3h-5h; finally heating to 850-950°C at a heating rate of 3°C / min and keeping warm for 12-18h.

[0016] In a further embodiment, the sodium source includes one or more of sodium carbonate, sodium acetate, sodium oxalate, sodium citrate, sodium hydroxide and sodium nitrate;

[0017] The iron source is one or more of ferric oxide, ferroferric oxide, ferrous oxide or ferric nitrate;

[0018] The nickel source is one or more of nickel trioxide, nickel nitrate, nickel chloride, nickel hydroxide and nickel acetate;

[0019] The manganese source is one or more of manganese dioxide, manganese acetate, manganese chloride, manganese nitrate and manganese perchlorate;

[0020] The titanium source is one or more of titanium dioxide, titanium oxalate, titanium nitrate and titanium hydroxide;

[0021] The cobalt source is one or more of cobalt trioxide, cobalt nitrate, cobalt hydroxide and cobalt acetate;

[0022] The tin source is one or both of tin oxide and tin dioxide.

[0023] The third invention objective of the present invention is to provide a sodium ion battery, comprising a positive electrode sheet, wherein the positive electrode sheet contains the above-mentioned dual-phase composite sodium ion battery positive electrode material.

[0024] In a further embodiment, the positive electrode sheet also includes a conductive additive and a binder, and the mass ratio of the dual-phase composite sodium ion battery positive electrode material, the conductive additive and the binder is 8:1:1 or 7:2:1.

[0025] The preparation method of the positive electrode sheet is: mixing and grinding the dual-phase composite sodium ion battery positive electrode material with the conductive additive and the binder in a mass ratio; adding NMP solvent drop by drop into the grind to prepare a positive electrode slurry; then using a coating machine to evenly coat the positive electrode slurry on an aluminum foil, and drying it in a vacuum oven; and finally cutting it into positive electrode sheets.

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] The dual-phase composite sodium ion battery positive electrode material prepared by the present invention is a high entropy layered oxide, and by adjusting the doping ratio of Sn, a layered oxide positive electrode material in which O3 phase and P2 phase are mixed in different ratios is obtained. And the interlayer spacing and bond energy of the positive electrode material are adjusted together with the high entropy effect, thereby improving the cycle stability of the positive electrode material.

[0028] The increase of Sn content in the positive electrode material of the dual-phase composite sodium ion battery prepared by the present invention increases the proportion of the P2 phase in the material. When the Sn element 0<1-yzuvw≤0.06, the mass ratio of the P2 phase to the O3 phase is 15:85-25:75, which can improve the cycle performance of the material. When the molar content of Sn accounts for 2% of the molar amount of all elements in the transition metal layer, the material Na 0.9 Fe 0.2 Ni 0.2 Mn 0.2 Ti 0.2 Co 0.18 Sn 0.02 The performance of O2 was improved the most, with the ratio of P2 phase to O3 phase being 19.46:80.52. The reversible discharge capacity of the battery assembled with the material in the first week reached 113.92 mAh / g; after 100 cycles, the capacity retention rate was 61.38%, which was 15.28% higher than that of the undoped Sn material battery.

[0029] The present invention performs three-stage calcination on the precursor, thereby ensuring that each reactant is fully diffused below the melting point, and improving the cycle stability of the dual-phase composite sodium ion battery positive electrode material. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is an electron microscope scanning image of the dual-phase composite sodium ion battery positive electrode material prepared in Example 1;

[0031] Figure 2 XRD patterns of materials prepared in Examples 1, 2, 3 and Comparative Example 1;

[0032] Figure 3 The charge and discharge curves of the positive electrode materials of Example 1 (left figure) and Comparative Example 1 (right figure);

[0033] Figure 4 The cycle diagram of the positive electrode materials prepared in Examples 1-3 and Comparative Example 1. DETAILED DESCRIPTION

[0034] The present invention is further described in detail below through specific examples. The following examples are only illustrative and not restrictive, and the protection scope of the present invention cannot be limited thereto.

[0035] The purity of the sodium carbonate, ferric oxide, nickel oxide, manganese dioxide, titanium dioxide, cobalt oxide, tin oxide, organic solvent and sodium flakes used in the examples is not less than 99%.

[0036] In the present invention, the conductive additive may be acetylene black, conductive carbon black (super p) or Ketjen black; the binder may be polyvinylidene fluoride (PVDF).

[0037] The electrolyte used in the sodium ion battery includes but is not limited to the organic electrolyte commonly used in sodium ion batteries: 1 mol / L NaClO4 dissolved in 1:1 ethylene carbonate (EC): diethyl carbonate (DEC), and an electrolyte with 5 vol% or 10 vol% fluoroethylene carbonate (FEC) additive added.

[0038] Embodiment 1:

[0039] This example prepares a dual-phase composite sodium ion battery positive electrode material with a chemical formula of Na 0.9 Fe 0.2 Ni 0.2 Mn 0. 2Ti 0.2 Co 0.18 Sn 0.02 O2, wherein the ratio of P2 phase to O3 phase is 19.46:80.52, and the preparation method is:

[0040] According to the stoichiometric ratio, 0.023175 mol Na2CO3, 0.005 mol Fe2O3, 0.005 mol Ni2O3, 0.01 mol MnO2, 0.01 mol TiO2, 0.0045 mol Co2O3 and 0.001 mol SnO were weighed and poured into a stainless steel ball mill, 60 ml acetone was added as a dispersant, and the mixture was ball milled at 400 r / min for 4 h using a planetary ball mill; the ball-milled material was then dried in a 70°C forced air drying oven for 12 h to obtain a precursor.

[0041] The precursor powder was placed in a muffle furnace and heated to 300°C at a heating rate of 3°C / min under air atmosphere and kept warm for 3 hours, then heated to 500°C at a heating rate of 3°C / min and kept warm for 3 hours, and finally heated to 850°C at a heating rate of 3°C / min and kept warm for 15 hours; then cooled to 100°C in the furnace, taken out, and immediately placed in an argon glove box for storage for later use.

[0042] Figure 1 The Na prepared in this example 0.9 Fe 0.2 Ni 0.2 Mn 0.2 Ti 0.2 Co 0.18 Sn0.02 Scanning electron microscope image of O2 material, Figure 1 This shows that the particle size distribution of the material is relatively uniform, about 1 μm.

[0043] Figure 2 The XRD diagram of the material, in which PDF#52-0689 is the XRD standard card of the P2 phase, and PDF#54-0887 is the XRD standard card of the O3 phase. By comparison, it is found that the XRD diagrams of the materials prepared in Examples 1-3 and Comparative Example 1 have both O3 phase peaks and P2 phase peaks, indicating that they are both dual-phase structures.

[0044] That is, the positive electrode material prepared in Example 1 is a material in which O3 phase and P2 phase are mixed, and the mass proportion of P2 phase is 19.46%.

[0045] Application Example 1:

[0046] The dual-phase composite sodium ion battery positive electrode material prepared in Example 1 was mixed with conductive carbon black and PVDF in a mass ratio of 8:1:1, ground, and NMP solvent was added dropwise to prepare a positive electrode slurry; then the positive electrode slurry was evenly coated on an aluminum foil using a coating machine, and dried in a vacuum oven at 100°C for 12 hours; finally, it was cut into positive electrode sheets with a diameter of 14 mm.

[0047] The positive electrode sheet, sodium sheet, electrolyte and battery shell are assembled into a CR2032 button battery, wherein the electrolyte is 1 mol L -1 NaClO4 is dissolved in 1:1 EC / DEC; the sodium sheet is used as the negative electrode and the diaphragm is made of glass fiber.

[0048] The button battery prepared above was subjected to charge and discharge tests using a Xinwei CT-3008-5V1mA-164 charge and discharge test system with a test window of 1.5V-4.0V and a 1C current density of 100mA / g.

[0049] like Figure 3 As shown in the figure on the left, at a current density of 0.1C, the first-week discharge capacity of the battery is 113.93mAh / g; Figure 4 As shown, after 100 cycles at 1C current density, the capacity retention rate of the battery is 61.38%.

[0050] Embodiment 2:

[0051] This example synthesized a dual-phase composite sodium ion battery cathode material with a chemical formula of Na 0.9 Fe 0.2 Ni 0.2 Mn 0.2 Ti 0. 2Co 0.16 Sn 0.04O2, in which the ratio of P2 phase to O3 phase is 20.40:79.60.

[0052] The difference from Example 1 is that the Sn content is further increased, and the preparation method is as follows:

[0053] According to the stoichiometric ratio, 0.023175 mol Na2CO3, 0.005 mol Fe2O3, 0.005 mol Ni2O3, 0.01 mol MnO2, 0.01 mol TiO2, 0.004 mol Co2O3 and 0.002 mol SnO were weighed and poured into a stainless steel ball mill. 60 ml of acetone was added as a dispersant. The mixture was ball milled at 400 r / min for 4 h using a planetary ball mill. The ball-milled material was then dried in a 70°C forced air drying oven for 12 h to obtain a precursor.

[0054] The precursor powder was placed in a muffle furnace and heated to 350°C at a heating rate of 3°C / min in an air atmosphere and kept at that temperature for 4 hours. The temperature was then increased to 550°C at a heating rate of 3°C / min and kept at that temperature for 4 hours. Finally, the temperature was increased to 900°C at a heating rate of 3°C / min and kept at that temperature for 18 hours. The powder was then cooled to 100°C in the furnace, taken out, and immediately placed in an argon glove box for storage.

[0055] like Figure 2 ZhongNa 0.9 Fe 0.2 Ni 0.2 Mn 0.2 Ti 0.2 Co 0.16 Sn 0.04 The XRD diagram of O2 shows that the prepared positive electrode material is a mixture of O3 phase and P2 phase, and the content of P2 phase is further increased to 20.40%.

[0056] Application Example 2:

[0057] The dual-phase composite sodium ion battery positive electrode material prepared in Example 2 was mixed with acetylene black and PVDF in a mass ratio of 7:2:1, ground, and NMP solvent was added dropwise to prepare a positive electrode slurry; the positive electrode slurry was evenly coated on an aluminum foil using a coating machine, dried in a vacuum oven at 100°C for 12 hours, and then cut into positive electrode sheets with a diameter of 14 mm.

[0058] As in Application Example 1, the positive electrode sheet, sodium sheet, electrolyte and battery shell are assembled into a CR2032 button battery, and the same method is used to perform charge and discharge tests on the battery.

[0059] The battery's first-week discharge capacity at 1C current density was found to be 87.33 mAh / g. Figure 4As shown, after 100 cycles at 1C current density, the capacity retention rate of the battery is 59.11%.

[0060] Embodiment 3:

[0061] This example synthesized a dual-phase composite sodium ion battery cathode material with a chemical formula of Na 0.9 Fe 0.2 Ni 0.2 Mn 0.2 Ti 0. 2Co 0.14 Sn 0.06 O2, wherein the ratio of P2 phase to O3 phase is 21.44:78.56. The difference from Example 2 is that the content of Sn is further increased, and the synthesis method is:

[0062] According to the stoichiometric ratio, 0.023175mol Na2CO3, 0.005mol Fe2O3, 0.005mol Ni2O3, 0.01mol MnO2, 0.01mol TiO2, 0.0035mol Co2O3 and 0.003mol SnO were weighed and poured into a stainless steel ball mill, 60ml acetone was added as a dispersant, and the ball mill was used for 4h at a speed of 400r / min with a planetary ball mill, and then the ball-milled material was dried in a 70℃ forced air drying oven for 12h to obtain a precursor. The precursor powder was placed in a muffle furnace, heated to 300℃ at a heating rate of 3℃ / min in an air atmosphere for 3h, then heated to 500℃ at 3℃ / min and kept for 3h, and finally heated to 850℃ at 3℃ / min and kept for 15h, then cooled to 100℃ with the furnace and taken out, and immediately placed in an argon glove box for storage.

[0063] like Figure 2 ZhongNa 0.9 Fe 0.2 Ni 0.2 Mn 0.2 Ti 0.2 Co 0.14 Sn 0.06 The XRD pattern of O2 shows that the prepared positive electrode material is a mixture of O3 phase and P2 phase.

[0064] Application Example 3:

[0065] The dual-phase composite sodium ion battery positive electrode material prepared in Example 3 was mixed with conductive carbon black and PVDF in a mass ratio of 8:1:1 and ground, and NMP solvent was added dropwise to prepare a positive electrode slurry; the positive electrode slurry was evenly coated on an aluminum foil using a coating machine, and dried in a vacuum oven at 100°C for 12 h, and then cut into positive electrode sheets with a diameter of 14 mm.

[0066] As in Application Example 1, the positive electrode sheet, sodium sheet, electrolyte and battery shell are assembled into a CR2032 button battery, and the same method is used to perform charge and discharge tests on the battery.

[0067] The battery's first-week discharge capacity at 1C current density was found to be 70.2mAh / g. Figure 4 As shown, after 100 cycles at a current density of 1C, the capacity retention rate of the battery is 55.7% (39 / 70.02=0.5569837189).

[0068] Comparative Example 1:

[0069] This comparative example synthesized a dual-phase composite sodium ion battery positive electrode material with a chemical formula of Na 0.9 Fe 0.2 Ni 0.2 Mn 0. 2Ti 0.2 Co 0.2 O2.

[0070] The preparation method is the same as that of Example 1, except that Sn is not used to replace part of Co. The synthesis method is:

[0071] According to the stoichiometric ratio, 0.023175 mol Na2CO3, 0.005 mol Fe2O3, 0.005 mol Ni2O3, 0.01 mol MnO2, 0.01 mol TiO2 and 0.005 mol Co2O3 were weighed, with 3% excess Na2CO3, poured into a stainless steel ball mill, 60 ml acetone was added as a dispersant, and the mixture was ball-milled at 400 r / min for 4 h using a planetary ball mill, and then the ball-milled material was dried in a 70°C forced air drying oven for 12 h to obtain a precursor.

[0072] The precursor powder was placed in a muffle furnace and heated to 300°C at a heating rate of 3°C / min in an air atmosphere and kept warm for 3 hours. The temperature was then increased to 500°C at a heating rate of 3°C / min and kept warm for 3 hours. Finally, the temperature was increased to 850°C at a heating rate of 3°C / min and kept warm for 15 hours. The powder was then cooled to 100°C in the furnace, taken out, and immediately placed in an argon glove box for storage.

[0073] like Figure 2 ZhongNa 0.9 Fe 0.2 Ni 0.2 Mn 0.2 Ti 0.2 Co 0.2 The XRD diagram of O2 shows that the prepared positive electrode material is a high-entropy layered oxide material mixed with O3 phase and P2 phase, in which the ratio of P2 phase to O3 phase is 18.20:81.80.

[0074] Application Comparative Example 1:

[0075] The positive electrode sheet was made in the same manner as in Application Example 1, and then assembled into a CR2032 button battery, and the same method was used to perform charge and discharge tests on the battery.

[0076] After testing, Figure 3 As shown in the figure on the right, the battery has a discharge capacity of 104.57 mAh / g in the first week at a current density of 0.1C. Figure 4 As shown, after the battery is cycled 100 times at a current density of 1C, the capacity retention rate is 46.10%, which is significantly lower than that in Example 1.

[0077] It can be seen from the above three embodiments and comparative examples that the use of Sn doping in the dual-phase composite sodium ion battery positive electrode material prepared by the present invention can improve the cycle performance of the material. By adjusting the doping ratio of Sn, a positive electrode material mixed with O3 phase and P2 phase layered oxides in different proportions is obtained. And with the increase of the Sn doping amount, the cycle performance of the material first increases and then decreases, so the molar content of Sn in this application is preferably 0.1-6%, and the mass ratio of P2 phase and O3 phase is 15:85~25:75, which can achieve the purpose of improving the performance of the material. In addition, the present application also works together with the high entropy synergistic effect to regulate the interlayer spacing and bond energy of the positive electrode material, thereby further improving the cycle stability of the positive electrode material.

[0078] The use of sodium source, iron source, nickel source, manganese source, titanium source, cobalt source and tin source in the present application are all conventional choices in the art and do not limit the scope of protection of the present invention.

[0079] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A dual-phase composite sodium ion battery positive electrode material, characterized in that: It has a P2 / O3 two-phase composite structure with the chemical formula Na 1-x Fe y Ni z Mn u Ti v Co w Sn 1-y-z-u-v-w O2, where 0 < x < 1, 0 < y, z, u, v, w are all less than 1 and greater than 0, and the elements Fe, Ni, Mn, Ti, Co, and Sn are in the same transition metal layer and arranged disorderly.

2. The dual-phase composite sodium ion battery positive electrode material according to claim 1, characterized in that: x is 0.05~0.3, y is 0.1~0.3, z is 0.1~0.3, u is 0.1~0.3, v is 0.1~0.3, w is 0.1~0.3, 0<1-yzuvw≤0.

3.

3. The dual-phase composite sodium ion battery positive electrode material according to claim 2, characterized in that: w is 0.14~0.18, 0<1-yzuvw≤0.

06.

4. The dual-phase composite sodium ion battery positive electrode material according to claim 1, characterized in that: The mass ratio of the P2 phase to the O3 phase is 15:85 to 25:

75.

5. The method for preparing a dual-phase composite sodium ion battery positive electrode material according to any one of claims 1 to 4, characterized in that: The following steps are involved: (1) adding a sodium source, an iron source, a nickel source, a manganese source, a titanium source, a cobalt source and a tin source into a dispersant and mixing them by ball milling, and drying the mixture to obtain a precursor; (2) The precursor is calcined, then cooled to 100° C. in the furnace, and immediately transferred to an argon glove box to obtain a dual-phase composite sodium ion battery positive electrode material.

6. The preparation method according to claim 5, characterized in that: In step (1), the dispersant is acetone, ethanol or toluene, and the ball milling mixing time is 4 to 10 hours.

7. The preparation method according to claim 5, characterized in that: In step (2), the calcination is a three-stage calcination, specifically: heating to 300°C-400°C at a heating rate of 3°C / min in an air atmosphere and keeping warm for 3h-5h; then heating to 500°C-600°C at a heating rate of 3°C / min and keeping warm for 3h-5h; finally heating to 850-950°C at a heating rate of 3°C / min and keeping warm for 12-18h.

8. The preparation method according to claim 5, characterized in that: The sodium source includes one or more of sodium carbonate, sodium acetate, sodium oxalate, sodium citrate, sodium hydroxide and sodium nitrate; The iron source is one or more of ferric oxide, ferroferric oxide, ferrous oxide or ferric nitrate; The nickel source is one or more of nickel trioxide, nickel nitrate, nickel chloride, nickel hydroxide and nickel acetate; The manganese source is one or more of manganese dioxide, manganese acetate, manganese chloride, manganese nitrate and manganese perchlorate; The titanium source is one or more of titanium dioxide, titanium oxalate, titanium nitrate and titanium hydroxide; The cobalt source is one or more of cobalt trioxide, cobalt nitrate, cobalt hydroxide and cobalt acetate; The tin source is one or both of tin oxide and tin dioxide.

9. A sodium ion battery, comprising a positive electrode sheet, characterized in that: The positive electrode sheet comprises the dual-phase composite sodium ion battery positive electrode material according to any one of claims 1 to 4.

10. A sodium ion battery according to claim 9, characterized in that: The positive electrode sheet also includes a conductive additive and a binder. The mass ratio of the dual-phase composite sodium ion battery positive electrode material, the conductive additive and the binder is 8:1:1 or 7:2:1.

Citation Information

Patent Citations

  • O3-type high-entropy sodium-ion battery positive electrode material, preparation method thereof and application of O3-type high-entropy sodium-ion battery positive electrode material in sodium-ion battery

    CN115863626A

  • Preparation method of two-phase proportion-adjustable high-entropy positive electrode material sodium ion battery

    CN116207359A

  • High-entropy doped O3 phase layered oxide and preparation method thereof, sodium ion battery positive electrode material and battery

    CN116605918A

  • Sodium-ion battery positive electrode material as well as preparation method and application thereof

    CN117096331A

  • High-entropy composite-phase positive electrode material with monocrystal-like morphology and preparation method of high-entropy composite-phase positive electrode material

    CN117174895A